Fractional-Order Fourier Analysis of the DNA - Tenreiro Machado, J. A. (2013)
This paper studies the deoxyribonucleic acid (DNA) code in the perspective of system dynamics and Fractional Calculus (FC). DNA includes the history of evolution towards the particular species and the instructions for the growth of each individual during its lifetime. In this study are associated logical and mathematical concepts namely, alphabet coding, Fourier transform and FC for the analysis of the DNA data of di erent chromosomes. The results reveal important characteristics motivating further research with the formalisms of system dynamics.